If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 0.2(60) + 0.5x = 0.1(60 + x) Multiply 0.2 * 60 12 + 0.5x = 0.1(60 + x) 12 + 0.5x = (60 * 0.1 + x * 0.1) 12 + 0.5x = (6 + 0.1x) Solving 12 + 0.5x = 6 + 0.1x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-0.1x' to each side of the equation. 12 + 0.5x + -0.1x = 6 + 0.1x + -0.1x Combine like terms: 0.5x + -0.1x = 0.4x 12 + 0.4x = 6 + 0.1x + -0.1x Combine like terms: 0.1x + -0.1x = 0.0 12 + 0.4x = 6 + 0.0 12 + 0.4x = 6 Add '-12' to each side of the equation. 12 + -12 + 0.4x = 6 + -12 Combine like terms: 12 + -12 = 0 0 + 0.4x = 6 + -12 0.4x = 6 + -12 Combine like terms: 6 + -12 = -6 0.4x = -6 Divide each side by '0.4'. x = -15 Simplifying x = -15
| a^3-3a^2+2a+9=0 | | 295=r/51 | | m/98=43 | | 64382=39y | | 210x=4119 | | 6w^2-37w-35=0 | | 81x^2y^-2/3 | | 3x+1x= | | 56b^2+b+1=0 | | 10/11x=120 | | 7d^2-22d+16=0 | | x(60-x)=0 | | x+3.3=7.7 | | -4(7-8x)=-8-28 | | -23+13m=-14-5m | | v-847=1256 | | c=22 | | 3240+y=7735 | | 15d-2d= | | 2x+35=3x-5 | | 6309=4120+p | | 33x+40x=144 | | 4(x-9)=12 | | m-483=1703 | | -5x/7-2-9 | | 1/4(2x-6)=8 | | 8/x=55 | | 2(t-5)-3(2t-7)=12-5(3+11) | | 0.82=logx | | 11x-5x+-10=6x+5 | | 2x+(3x+25)=180 | | 320+-80x=0 |